Pola Spasial Daya Dukung Sumber Daya Air Di Kecamatan Driyorejo Kabupaten Gresik - Suning, Suning; Alholis, Haris Din (Universitas Dr. Soetomo, 2021)
The Regional Disaster Management Agency (BPBD) of Gresik Regency in 2019 stated that some villages in the Driyorejo District, Gresik Regency experienced drought, this condition is in contrast to the availability of water in 2012. The purpose of this study is to determine the spatial pattern of the carrying capacity of water resources. and direction of control policies for the carrying capacity of water resources. The research method used quantitative and qualitative descriptive analysis with the analysis technique of Water Bearing Capacity (DDA), Analytical Hierarchy Process (AHP) and spatial analysis using Arcgis 10.1 Software. Data collection techniques in the form of observation, documentation, questionnaires and agency surveys. The results showed that the water carrying capacity in Driyorejo District was 99.7% surplus and 0.3% deficit. The status of deficit water carrying capacity is in Petiken and Mojosarirejo Villages, especially in the industrial and service trade sectors. The main priority for the direction of the water carrying capacity control policy based on AHP is to improve land rehabilitation, development of infrastructure and improve the quality and quantity of water sources with scores of 161.4, 98 and 40.6, respectively.